Association Between Overt and Subtle Experiences of Discrimination and Violence and Mental Health in Homosexual and Bisexual Men in Mexico - Mendoza-Perez, Juan C. (Journal of interpersonal violence, 2021)
The aim of this study was to determine whether the experiences of direct or subtle forms of discrimination and violence are associated with mental health in Mexican gay, homosexual, and bisexual (GHB) men. A cross-sectional survey was conducted online; the sample consisted of 4,827 GHB men. Ten forms of overt and subtle sexual orientation–based discrimination and violence (SO-DV) were assessed. Linear and logistic regression models were used to evaluate the association between SO-DV experiences and mental health outcomes. Physical violence was reported less frequently than the other forms of SO-DV. As the number of settings in which SO-DV were experienced increased, a stronger association with negative mental health outcomes was observed. Experiences of subtle SO-DV were associated with increased distress, lower vitality, and increased risk of suicidal ideation. Disapproval of gender nonconformity was associated with negative mental health outcomes independently of violence based on sexual orientation. Subtle forms of SO-DV are more common than direct and overt forms. Both types of SO-DV could negatively affect mental health. Studies investigating these negative experiences are required to gain an understanding of the health inequalities faced by non-heterosexual populations.